Genomic-wide transcriptional profiling in primary myoblasts reveals Runx1-regulated genes in muscle regeneration - Umansky, Kfir Baruch (Genom Data, 2015)
In response to muscle damage the muscle adult stem cells are activated and differentiate into myoblasts that regenerate the damaged tissue. We have recently showed that following myopathic damage the level of the Runx1 transcription factor (TF) is elevated and that during muscle regeneration this TF regulates the balance between myoblast proliferation and differentiation (Umansky et al.). We employed Runx1-dependent gene expression, Chromatin Immunoprecipitation sequencing (ChIP-seq), Assay for Transposase-Accessible Chromatin with high-throughput sequencing (ATAC-seq) and histone H3K4me1/H3K27ac modification analyses to identify a subset of Runx1-regulated genes that are co-occupied by the TFs MyoD and c-Jun and are involved in muscle regeneration (Umansky et al.). The data is available at the GEO database under the superseries accession number GSE56131.